Population information - United Nations (Asia-Pacific Population Journal, 1988)
Information plays a critical role in changing people’s and Governments’ attitudes about population issues. Because information is considered one of the pillars upon which the success of population policies and programmes is based, the United Nations Economic and Social Commission for Asia and the Pacific (ESCAP) made it a priority area of its population activities since the formation of its Clearing-house and Information Section as part of the Population Division.